Perancangan Sistem Pencegahan Pencurian Kendaraan Bermotor Berbasis ESP32 pada PT. Suwarna Dwipa Maju - Jonas, Dendy; Supriyono, Ignatius Agus; Junianto, Hendri (Technomedia Journal, 2022)
The rise of acts of thievery among users of two-wheeled vehicles has become a problem for motorists. According to the Indonesian Central Statistics Agency (BPS) in the 2020 Criminal Statistics report, the crime of motor vehicle theft without the use of violence in 2019 was 80,450 incidents and the crime of motor vehicle theft with the use of violence was 7,321 incidents. Apart from the loss of a vehicle, sometimes burglary can result in motorists being injured and not a few losing their lives. Currently, two-wheeled vehicles are generally not equipped with a smart key that can function as a circuit breaker and a tool for monitoring the vehicle's position. This is because the implementation of the system costs money and only applies to luxury two-wheeled vehicles. For this reason, an additional safety device is needed to increase the safety of the motorized vehicle. The design of this ESP32-based motor vehicle security system implements a smart key using the BLE (Bluetooth Low Energy) connection owned by ESP32 with the BLE device (Smartband, iTAG), GPS (Global Positioning System) Ublox Neo 6M to monitor the vehicle's position , 800L SIM for internet connection to database, 5V DC Relay for connecting/disconnecting motor vehicle ignition lines, Tactile Switch for sending emergency SMS and LM 2596 stepdown as a voltage reducer from 12V to 3.7V battery for power supply from the ESP32 itself.